Navigating the gender structure in information technology: How does this affect the experiences and behaviours of women?. (March 2020) - Kenny, Etlyn J; Donnelly, Rory
How do women, outnumbered and outranked, navigate work and careers in information technology? Only one in six information technology (IT) specialists in the UK is female. Such extreme male dominance potentially gives rise to a gender structure that affects women's experiences of IT work. Using data from interviews with 57 technically skilled female IT professionals, we examine how women orient this gender structure and how they make sense of their gender identities as women working in IT. Our findings elucidate how the IT gender structure shapes women's careers in this field of work. They reveal how women use their agency to assert notions of femininity into technical careers, disentangle narratives around whether women have unique and different (but less technically focused) strengths in IT and interface with 'geek' and 'nerd' identities to achieve successful IT careers. In doing so, they provide insight into how technical women continue careers within a structure that externalises them through gender norms. This understanding can be used to aid efforts to retain women within IT as well as other fields facing similar challenges.